2017
DOI: 10.3390/ijms18112297
|View full text |Cite
|
Sign up to set email alerts
|

Old and New Biological Therapies for Psoriasis

Abstract: Biological therapy became available for psoriasis with the introduction of alefacept at the beginning of this century. Up to then, systemic treatment options comprised small molecule drugs, targeting the immune system in a non-specific manner. The first biologics targeted T-cell activation and migration and served as an alternative to small molecules. However, significant improvement in outcome was first accomplished with the introduction of tumor necrosis factor-α inhibitors that were already approved for oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
190
0
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(213 citation statements)
references
References 122 publications
(158 reference statements)
2
190
0
21
Order By: Relevance
“…Consistent with this genetic line of argumentation, microarray data, including ours, as well as big GWAS have mainly found aberrations in T‐cell and not B‐cell‐related pathways . Not least our immunofluorescence stainings revealed that B cells are rarely found in psoriatic skin as compared to the dense infiltrate of T cells providing one reason why B‐cell‐depleting therapies have not proven resounding success for the therapy of psoriasis in contrast to the successful target‐oriented therapies that are focused on T‐cell‐mediated pathways …”
Section: Discussionsupporting
confidence: 81%
“…Consistent with this genetic line of argumentation, microarray data, including ours, as well as big GWAS have mainly found aberrations in T‐cell and not B‐cell‐related pathways . Not least our immunofluorescence stainings revealed that B cells are rarely found in psoriatic skin as compared to the dense infiltrate of T cells providing one reason why B‐cell‐depleting therapies have not proven resounding success for the therapy of psoriasis in contrast to the successful target‐oriented therapies that are focused on T‐cell‐mediated pathways …”
Section: Discussionsupporting
confidence: 81%
“…Consequently, the long‐term safety and tolerability of any treatment are critical to effective prescribing. Early biologic agents for the treatment of psoriasis typically induced non‐specific immunosuppression, including agents targeting T‐cell activation and migration (efalizumab and alefacept, both of which have now been withdrawn) and anti‐TNF agents that target a key cytokine involved in most inflammatory and infectious processes in the body . TNF antagonists have been associated with increased risk of serious bacterial, viral and fungal infections in patients with psoriasis, including active tuberculosis and reactivation of latent tuberculosis infection .…”
Section: Introductionmentioning
confidence: 99%
“…Biologics inhibit the action of specific types of immune‐mediated cells, or inhibit the binding of proteins which play a role in the immune system in developing psoriasis, including pathways such as tumor necrosis factor (TNF)‐α, interleukin (IL)‐17A or IL‐23 . Among those targets, IL‐23/IL‐17 was detected as an immune axis and the discovery has brought further understanding of the role of cellular immunology in psoriasis .…”
Section: Introductionmentioning
confidence: 99%
“…The Psoriasis Area and Severity Index (PASI) is a well‐accepted scoring system used to evaluate the severity of psoriasis. A PASI‐90, interpreted as a 90% or more improvement from baseline PASI score, was adopted as the primary efficacy endpoint in recent clinical trial programs of biologics, and it was achieved in the majority of patients with the new biologics . Some biologics can demonstrate the attainment of even higher efficacy of PASI‐100 (i.e.…”
Section: Introductionmentioning
confidence: 99%